VALUASI EKONOMI MANFAAT AIR DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG, SULAWESI SELATAN - Nur Hayati; Abd Kadir Wakka (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
The potential of  water resources in Bantimurung Bulusaraung NP (Babul NP) can be utilized as a source of  ir rigation for rice fields farming , and fulfillment of  clean water for people in Maros, and surrounding areas. The importance of  resources are sometimes neglected, and appreciation of  it is ver y low due to lack of  information regarding how economic benefits generated by the resources for local communities and local government interests. The objective of  this research is to observe the economic value of  environmental water services in Babul NP. Economic valuation for household was done by procurement cost method; for drinking Regional Water Company by using simple financial analysis; for ir rigation water by using a different method in estimated calculated from the difference between productivity of irrigated-land with non-irrigated land; for micro-hydro by applying replacement market price method; for fisheries and car washing business by using contingen valuation method approach; for tourism pur pose calculation by using travel cost method. The results showed that the park has economic benefits value, amounting to 1,7 trillion rupiah per year for surrounding community, and for local government approximately 130 billion rupiah. The value of  economic benefits resulting from Babul NP is expected to be considered by all parties to participate in preserving Babul NP.